(untitled) (Praxis Educativa, 2025)
We reflect on the power of recovering the representational work that students of a Biology teacher training course carry out in class in order to learn about protein synthesis. With the aim of analysing the relationships between two external systems of representation –pictorial and oral– that lead to advances in knowledge when representations are taken as the object of analysis in class, we distinguish teaching interventions aimed at getting students to: identify how an anatomical arrangement collaborates with interpreting the functional; review marks included and link them to the functional; rethink ideas discussed that are difficult to assimilate; take up concepts already studied that generate doubts in a new context; and show what they did not manage to capture on paper. We maintain that these interventions address relationships between the figurative and the conceptual that contribute to the learning of specific content and the epistemic use of representational tools in the area. Keywords: Graphical representations, orality, external representation, science education, biology.